2011
DOI: 10.4103/0301-4738.86306
|View full text |Cite
|
Sign up to set email alerts
|

Structural sequelae and refractive outcome 1 year after laser treatment for type 1 prethreshold retinopathy of prematurity in Asian Indian eyes

Abstract: Aim:The aim was to study the structural sequelae and refractive outcome after laser treatment for Type 1 prethreshold retinopathy of prematurity (ROP) in Asian Indian eyes.Materials and Methods:A retrospective chart review of infants with Type 1 prethreshold ROP (defined according to the Early Treatment for Retinopathy of Prematurity study) undergoing laser treatment at a tertiary center between January 2004 and December 2008 was done. The 1-year outcome of infants was analyzed.Results:Sixty-nine eyes of 36 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 27 publications
(38 reference statements)
5
18
0
Order By: Relevance
“…It is a well-known fact that preterm children have higher rates of myopia and more so if they develop severe ROP requiring treatment. [ 7 8 9 10 ] Since the infants affected with severe ROP are on the rise with the third epidemic of the same,[ 18 ] soon there will be more children affected by myopia. The load of refractive errors and amblyopia will rise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is a well-known fact that preterm children have higher rates of myopia and more so if they develop severe ROP requiring treatment. [ 7 8 9 10 ] Since the infants affected with severe ROP are on the rise with the third epidemic of the same,[ 18 ] soon there will be more children affected by myopia. The load of refractive errors and amblyopia will rise.…”
Section: Discussionmentioning
confidence: 99%
“…Myopia is the most common refractive error in babies who have been treated for ROP with laser photocoagulation. [ 6 7 8 9 ] The prevalence of myopia in premature babies with or without ROP is reported to vary between 21% and 100%. [ 7 8 9 10 11 ] The cause of myopia and its anatomic correlates in these eyes is still to be adequately answered.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is difficult to compare different studies regarding the refractive outcome. When reviewing the literature on refractive error in children with ROP, we found that the prevalence of myopia differed between studies, with a range from 52.2% to 77% 11 , 13 , 16 , 17 ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%